American gastroenterological association consensus development conference on the use of biologics in the treatment of inflammatory bowel disease, June 21-23, 2006. - Clark, M; Colombel, J; Feagan, B; Fedorak, R; Hanauer, S; Kamm, M; Mayer, L; Regueiro, C; Rutgeerts, P; Sandborn, W; Sands, B; Schreiber, S; et al. (2007)
The American Gastroenterological Association (AGA) convened a panel of gastroenterologists expert in the area of inflammatory bowel disease (IBD) that developed this consensus statement based on expert presentations of current scientific knowledge about IBD and through subsequent group discussion. This statement reflects the panel's assessment of medical knowledge available when written. Thus, readers should view this statement in the context of data that will accumulate after its creation. The opinions, conclusions, and recommendations expressed in this report are those of the consensus panel members and may or may not reflect the official opinion of the American Gastroenterological Association Institute. The conference upon which this report is based was funded through an unrestricted educational grant from Abbott Laboratories. Abbott Laboratories representatives did not attend the conference, nor did they participate in any way in the development of this report.